Specialized educational and scientific center of Novosibirsk State University: the development of the educational model from the idea of the founders of Novosibirsk academic campus to the present - O. V. Nekrasova; A. V. Karpenko; L. A. Nekrasova (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. Since its establishment in 1963, the Specialized Educational and Scientific Center of Novosibirsk State University (SESC NSU) has focused on advanced subject-specific training and close collaboration with the academic community. Over time, the school has refined its organizational and digital frameworks, while maintaining a consistent emphasis on high-quality academic instruction and fostering students’ independent learning. These principles have served as the foundation for implementing innovative pedagogical practices. Goal. To outline the key milestones in the evolution of SESC NSU educational model and to demonstrate how the continuous integration of innovative approaches, while preserving core academic values, ensures exceptional outcomes in educating gifted students. Materials and Methods. The study employs a historical-pedagogical approach (analysis of archival documents, including curricula, directives, and reports), content analysis of regulatory acts, and a comparative analysis of statistical data on academic performance, Unified State Exam results, and Olympiad achievements of graduates. Results and discussion. The findings indicate that an evolutionary development paradigm stipulates retaining key components (advanced subject instruction, scientific mentorship, and a boarding-school format) while systematically integrating additional elements (digital tools, project-based research courses, and tutoring support). It enables SESC NSU to remain one of leading educational institutions in Russia. The boarding-school model also helps students develop self-management, leadership and teamwork skills. Conclusion. High academic performance, significant success in Olympiad competitions, and a high rate of admission to top universities underscore the effectiveness of SESC NSU educational model. These results demonstrate that combining fundamental educational principles with modern innovations creates a competitive system of specialized learning. This approach preserves the continuity of scientific traditions while contributing to the advancement of Russian education and science.